Sharia Compliant Factoring as an Instrument for Mitigating Hospital Liquidity Crises: A Juridical Analysis of the Hawalah bil Ujrah Scheme for BPJS Kesehatan Claim Receivables - Cintya Agustina Yuristasari; Muhammad Ma'rur; Moh. Zunaidi Halimi; Anggit Wasesa Praja; Anisa Al Azizi (JURNAL MAHASISWA YUSTISI, 2026)
The liquidity crisis faced by hospitals in Indonesia, caused by delayed and uncertain payment of BPJS Kesehatan claims, necessitates a financing instrument that is both effective and sharia-compliant. The hawalah bil ujrah scheme has been proposed as a solution for sharia-compliant factoring; however, its application to BPJS Kesehatan claim receivables raises three unresolved legal issues: the conformity of the contractual object with the dayn thabit (certain and fixed debt) requirement, the construction of the tripartite legal relationship among hospitals, Islamic financial institutions, and BPJS Kesehatan, and the legal protection of the parties following the assignment of the receivable. This study aims to analyze the juridical validity of applying hawalah bil ujrah to such claim receivables and to formulate an appropriate legal construction and regulatory direction. The study employs a normative juridical method with statutory, conceptual, and comparative approaches, analyzed through content analysis techniques. The findings indicate that, at the time of assignment, BPJS Kesehatan claim receivables fall within the category of dayn ghair mustaqir (unsettled debt), thereby posing a potential violation of the thubut (certainty) requirement, unless the assignment is confined to the portion of claims that has passed preliminary verification. The tripartite relationship within this scheme is likewise of a mixed civil-law and public-administrative nature, and is more accurately construed as hiwalah muqayyadah (restricted debt transfer). The study concludes that the scheme remains viable for implementation, provided it is accompanied by a restriction on the object of the contract, strengthened risk-allocation clauses, technical regulation on assignment notification, and a sharia-arbitration-based dispute resolution mechanism.